Evaluasi Program Pelatihan Service Air Conditioner Menggunakan Model CIPP Untuk Pemberdayaan Masyarakat Di PKBM Tim Suara Masyarakat Dawuan - Hayyan, Al Azzam Faizarush; Meilya, Ika Rizqi; Suminar, Uum (Universitas Pahlawan Tuanku Tambusai, 2025)
Improving vocational skills among community members has become a key focus in empowering those who are not accommodated by formal education. The PKBM Tim Suara Masyarakat Dawuan Cikampek initiated an air conditioner (AC) service training program as an alternative solution for residents to gain practical skills and opportunities for self-employment. This study aims to evaluate the implementation of the training program using the CIPP evaluation model (Context, Input, Process, Product). A descriptive qualitative approach was applied, with data collected through in-depth interviews, observation, and documentation. The research subjects included instructors, training participants, and program organizers. The findings reveal that: (1) in terms of context, the program is well-targeted, responding to the real needs of the community for technical skills; (2) in terms of input, the program has a fairly good planning structure, although improvements are still needed in facilities and practice tools; (3) in terms of process, the training was carried out effectively, despite facing challenges in time management and instructional methods; and (4) in terms of product, the program has successfully enhanced participants' knowledge and skills, with some graduates initiating their own service businesses. In conclusion, the AC service training program has made a positive contribution to community empowerment. However, further improvements are needed in input and process aspects to optimize and sustain the program's outcomes. Keywords: Program Evaluation, AC Service Training, Community Empowerment, CIPP Model, PKBM Improving vocational skills among community members has become a key focus in empowering those who are not accommodated by formal education. The PKBM Tim Suara Masyarakat Dawuan Cikampek initiated an air conditioner (AC) service training program as an alternative solution for residents to gain practical skills and opportunities for self-employment. This study aims to evaluate the implementation of the training program using the CIPP evaluation model (Context, Input, Process, Product). A descriptive qualitative approach was applied, with data collected through in-depth interviews, observation, and documentation. The research subjects included instructors, training participants, and program organizers. The findings reveal that: (1) in terms of context, the program is well-targeted, responding to the real needs of the community for technical skills; (2) in terms of input, the program has a fairly good planning structure, although improvements are still needed in facilities and practice tools; (3) in terms of process, the training was carried out effectively, despite facing challenges in time management and instructional methods; and (4) in terms of product, the program has successfully enhanced participants' knowledge and skills, with some graduates initiating their own service businesses. In conclusion, the AC service training program has made a positive contribution to community empowerment. However, further improvements are needed in input and process aspects to optimize and sustain the program's outcomes. Keywords: Program Evaluation, AC Service Training, Community Empowerment, CIPP Model, PKBM